Seaways and gatekeepers : trade and state in the eastern archipelagos of Southeast Asia, c.1600-c.1906 - Sutherland, Heather (NUS Press, 2021)
The eastern archipelagos of Southeast Asia stretch from Mindanao and Sulu in the north to Bali in the southwest and New Guinea in the southeast. Many of their inhabitants are regarded as ""people without history"", while colonial borders cut across shared underlying patterns of relations. Yet many of these societies were linked to trans-oceanic trading systems for millennia. Indeed, some of the world's most prized commodities once came from territories which were either ""stateless"" or under the tenuous control of loosely structured polities in this region.Trade provides the integrating frame.